An Analysis of The Effectiveness of online and Hybrid Learning Models in Indonesian Language Courses - Asih Andriyati Mardliyah; Amy Krisdiana; Suesthi Rahayuningsih (Indonesian language and literature education program Majapahit Islamic University, 2024)
The aim of this research is to reveal the effectiveness of online learning at the Universitas Terbuka and the effectiveness of hybrid learning at the Majapahit Islamic University. This research uses qualitative research with a descriptive approach. The researchers use survey and observation as data collection. The data that has been collected is analyzed using Miles and Huberman's interactive analysis techniques. The results of this research show that online learning and hybrid learning have a positive impact, namely (1) students are helped in learning activities, (2) students are helped in understanding the material provided by the lecturer, (3) students are more interested and can take part in online and hybrid learning well. (4) there are obstacles or limitations in terms of technology that disrupt students when doing online or hybrid learning, but the majority of students are not disturbed when doing online or hybrid learning. From the results of the research above, it can be concluded that in general online learning at the Universitas Terbuka and hybrid learning at the Islamic University of Majapahit have been running quite effectively. Keywords: Effectiveness; Online Learning; Hybrid Learning